Близкий друг: [для сред. шк. возраста ] / Сестры Воробей - Сестры Воробей (Романы для девочек, 2003)
Экземпляры: ф. 6 (20140224) / Инвентарный номер: 35768 / Цена: 18.00 / Авт.знак: С 33 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6